Open Space Mathematical Model for the Mobile Satellite L-Band Signal in Sarawak using Global Positioning System Technology - Voon Pai, B.; Abidin, W.A.W.Z; Zen, H.; Masri, T.; Abdullah, M. (IEEE, 2011)
The effect of ionosphere on mobile satellite (MS) L-band signal which are propagated from the transmitting satellite to the receiver over the equatorial region has attracted much interest. Sarawak which is located near the equatorial region has been selected for the purpose of this research. By means of data acquisition system using the Global Positioning System (GPS) technology, data measurement and analysis has been carried out at the Universiti Malaysia Sarawak campus in early months of 2010. The results have been presented in the forms of received signal performance, fading characteristics and complementary cumulative distribution function of certain GPS satellites over the sky of Sarawak. A general mathematical model representing the signal strength for the open space environment in equatorial region has been developed. The availability of more satellite propagation data in different places of equatorial region will improve the MS model and quality of service perceived by MS users.